The View of the Yeti : Bringing up children in the spirit of self-awareness and kindredship - Vandenbroeck, Michel (Bernard van Leer Foundation, 1999)
Using the mythical creature of the Himalayas, the Yeti, as a symbol for the prejudices and assumptions that people prematurely make about each other, this book discusses bringing up children to accept and cherish diversity and helping them to thrive in an increasingly diverse world. Directed to educators and caregivers of toddlers and preschoolers, the book takes insights from Dutch-, French-, and English-language literature and provides practical examples based on European issues and context. Chapters 1 and 2 deal with facilitating identity development in a fragmented world. Chapters 3 and 4 examine self-image development and the image of the "other." Chapter 5 looks at an educational model based on the social and developmental psychology insights from previous chapters. Chapters 6 and 7 examine parental cooperation and suggest some ways that the educational model can be implemented at educational centers. Chapter 8 analyzes multilingualism. Chapter 9 examines how a group in a child care center or elementary school can be equipped and organized. The book's appendix highlights legal regulations that parents and educators must follow and includes the mission and mandate embodied in the U.N.'s Treaty for the Rights of the Child. (Contains 190 references.) (KB)